Work to welfare : how men become detached from the labour market - Alcock, Peter, 1951- (Cambridge University Press, 2003)
In recent years vast numbers of men have moved completely out of the labour market into 'early retirement' or 'long-term sickness' and taken on new roles in the household. Based on new research the book explores the varied circumstances they are living in and challenges assumptions about the labour market.